2020
DOI: 10.1021/acs.jnatprod.0c00758
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Furancarboxylic Acids from a Penicillium sp.

Abstract: Ten novel (1, 2, 3a, 3b, 4a, 4b, 5a, 5b, 6a, and 6b) furancarboxylic acids including four pairs of epimers (3a, 3b; 4a, 4b; 5a, 5b; 6a, 6b), together with seven known analogues (7a, 7b, 8a, 8b, 9a, 9b, and 10), were isolated from the fermentation of the soil-derived fungus Penicillium sp. sb62. Their structures were established on the basis of spectroscopic data analysis, and the absolute configurations were determined by time-dependent density functional theory electronic circular dichroism calculations, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 19 publications
2
28
0
1
Order By: Relevance
“…They possessed antimicrobial capacities versus E. coli, S. aureus, and C. albicans with MICs 0.9-7.0, 1.7-3.5, and 3.3-7.0 µg/mL, respectively, in the broth microdilution assay. It was observed that the absence of methoxy or a hydroxy substituent on the side chain enhanced the activity similar to 89 and 90, and the configurations of the methoxy or hydroxy groups on the side chain had a little effect as in 91, 92, 93, and 94 [16].…”
Section: Antimicrobial Activitymentioning
confidence: 97%
See 3 more Smart Citations
“…They possessed antimicrobial capacities versus E. coli, S. aureus, and C. albicans with MICs 0.9-7.0, 1.7-3.5, and 3.3-7.0 µg/mL, respectively, in the broth microdilution assay. It was observed that the absence of methoxy or a hydroxy substituent on the side chain enhanced the activity similar to 89 and 90, and the configurations of the methoxy or hydroxy groups on the side chain had a little effect as in 91, 92, 93, and 94 [16].…”
Section: Antimicrobial Activitymentioning
confidence: 97%
“…The relative configuration was determined by NOESY and ROESY (rotating frame Overhauser effect spectroscopy), as well as by [α] D measurement [34]. The exciton coupled circular dichroism (ECCD) analysis and electronic circular dichroism (ECD) calculations were utilized to assess the absolute configuration by comparing the theoretical and experimental CD spectra [16,17,37,49]. Additionally, the determination of the absolute configuration was carried out using Mosher's method and analyzing chemical shift differences between (S)-and (R)-MTPA [16].…”
Section: Structural Characterization Of Thiophenesmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The isolation, chemical synthesis, structural revision, and biosynthesis of these compounds have always attracted chemists and biochemists. [6][7][8][9][10][11][12] For example, gregatin A, was isolated in 1975 and its structural determination was finally achieved in 2012 after two rounds of revisions. 9,12,13 Moreover, the biosynthesis of gregatin A involves the fusing of two different polyketide chains, which are synthesized by a single polyketide synthase.…”
Section: Introductionmentioning
confidence: 99%